2020
DOI: 10.3389/fcimb.2020.582187
|View full text |Cite
|
Sign up to set email alerts
|

Virome Sequencing of the Human Intestinal Mucosal–Luminal Interface

Abstract: While the human gut virome has been increasingly explored in recent years, nearly all studies have been limited to fecal sampling. The mucosal-luminal interface has been established as a viable sample type for profiling the microbial biogeography of the gastrointestinal tract. We have developed a protocol to extract nucleic acids from viruses at the mucosal-luminal interface of the proximal and distal colon. Colonic viromes from pediatric patients with Crohn's disease demonstrated high interpatient diversity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…Pregnant women with diabetes mellitus type 1 had a different composition of the virome as healthy pregnant women [ 291 ]. Most data of the virome exist from fecal samples, but studies with mucosal biopsies have recently been investigated for IBD [ 272 , 292 , 293 ]. Zuo et al found dysbiosis in IBD patients with increase of Caudovirales bacteriophages and was able to correlate dysbiosis with intestinal inflammation and functional impairment [ 292 ].…”
Section: Gut Viromementioning
confidence: 99%
“…Pregnant women with diabetes mellitus type 1 had a different composition of the virome as healthy pregnant women [ 291 ]. Most data of the virome exist from fecal samples, but studies with mucosal biopsies have recently been investigated for IBD [ 272 , 292 , 293 ]. Zuo et al found dysbiosis in IBD patients with increase of Caudovirales bacteriophages and was able to correlate dysbiosis with intestinal inflammation and functional impairment [ 292 ].…”
Section: Gut Viromementioning
confidence: 99%
“…They have been classified into 4 subfamilies and 10 genera. 23,27 Using similar methods, we were able to classify only 30 % of our crAss-like phages, with genera VI, VII and VIII being the most represented. In the Western population, the most common genus is I and in the Malawian cohorts, they are genera VIII and IX.…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effects of CsCl should be avoided to maintain diversity and integrity as much as possible. Additionally, even though sequencing has introduced a wealth of information regarding phage constituents within the microbiome [ 39 , 40 , 41 , 42 , 43 ], it has become apparent that there is a need to move into research that investigates the activity of said phage populations in relation to health and dysbiosis. As such, it is even more important to retain not only the community structure, but the activity.…”
Section: Discussionmentioning
confidence: 99%